PENGARUH PENEMPATAN PEGAWAI, DISIPLIN KERJA DAN KOMITMEN TERHADAP KINERJA PEGAWAI DI DINAS PEKERJAAN UMUM KOTA LUBUKLINGGAU - Veri Afriansyah; Yohanes Susanto; Sardiyo Sardiyo (Jurnal Media Ekonomi (JURMEK), 2020)
This research was conducted in Office of Public Works Lubuklinggau City. The purpose of research to determine the influence of employee placement, work discipline and commitment to employee performance in Office of Public Works Lubuklinggau City both simultaneously and partially. The sample in this research as many as 60 employees in Office of Public Works Lubuklinggau City. Data analysis technique used in this research is multiple linear regression test, coefficient of determination test, F test and t test. The results obtained are 1). The partial test (t test) performed proves employee placement has a significant effect on employee performance where tcount 4,419 > ttable 1,991 and also sig 0,009 < 0,05. 2). Work Discipline significantly influence the performance where tcount 6,436 > ttable 1,991 and also sig is 0,004 < 0,05. 3). Commitment significantly influence the performance where tcount 3,030 > ttable 1,991 and also sig is 0,026. 4). Employee Placement, Work Discipline and Commitment have significant influence simultaneously on Service in Office of Public Work Lubuklinggau City, where Fcount 4,518> Ftable 2,73 and also sig of 0,020 < 0.05.